Clinical pathways: development and implementation at a tertiary Hospital in Malaysia - Aniza Ismail,; Saperi Sulung,; Syed Mohamed AlJunid,; Nor Hamdan Mohd Yahaya,; Husyairi Harunarashid,; Oteh Maskon,; Andrea Ban,; Roslan Harun,; Ismail Mohd. Saiboon,; Ikafaizura Mohd. Nor, (Universiti Kebangsaan Malaysia, 2012)
Clinical pathways have been implemented in many healthcare systems with mix results in improving the quality of care and controlling the cost. CP is a methodology used for mutual decision making and organization of care for a well-defined group of patients within a well-defined period. In developing the CPs for a medical centre, several meetings had been carried out involving expert teams which consist of physicians, nurses, pharmacists and physiotherapists. The steps used to develop the pathway were divided into 5 phases. Phase 1: the introduction and team development, Phase II: determining the cases and information gathering, Phase III: establishing the draft of CP, Phase IV: is implementing and monitoring the effectiveness of CP while Phase V: evaluating, improving and redesigning of the CP. Four CPs had been developed: Total Knee Replacement (TKR), ST Elevation Myocardial Infarction (AMI), Chronic Obstructive Airways Diseases (COAD) and elective Lower Segment Caesarean Section (LSCS). The implementation of these CPs had supported the evidence-based medicine, improved the multidisciplinary communication, teamwork and care planning. However, the rotation of posts had resulted in lack of document ownership, lack of direction and guidance from senior clinical staff, and problem of providing CPs prior to admission. The development and implementation of CPs in the medical centre improved the intra and inter departmental communication, improved patient outcomes, promote patient safety and increased patient satisfaction. However, accountability and understanding of the CPs must be given more attention.